Konseling Kelompok Cognitive Behaviour Untuk Meningkatkan Konsep Diri Positif Siswa SMA - Putra, Rico Wardana; Christiana, Elisabeth; Habsy , Bakhrudin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
The benefits of CBT-based counseling services have been widely proven, one of which is through the implementation of this research that evaluated the effectiveness of CBT services in group counseling programs at the high school level to optimize their self-concept. By utilizing a true experimental study setting involving a number of students to carry out the intervention. Data processing went through multi-stage stages starting from paired sample T-test testing with a significance of 0.05. The research also conducted pretest and posttest stages to see differences in experimental results on the t-table, namely degrees of freedom (dk) N-1, and a significance of α = 0.05. The output of the data processing found a t-table value of 1.782, so Ha is "accepted". Findings through analysis of pre-treatment responses showed that students' self-concept was only in the medium category, and even 13 people had low self-concept. Meanwhile, the post-treatment value showed an increase with the post-test results of students who were not in the low group. The T-Test also showed a calculated t-value (7.597) which exceeded the t-table so that group counseling with CBT has been reliably able to improve respondents' negative self-concept and Ha is "accepted". Keywords: Cognitive Behavior Group Counseling, Positive Self Concept of Students.